Emergence in School Systems: Lessons from Complexity and Pedagogical Leadership - Alonso-Yanez, Gabriela; Preciado-Babb, Armando Paulino; Brown, Barbara; Friesen, Sharon (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2021)
The theoretical framework for this study draws on conceptual advances from two bodies of scholarship: 1) complexity thinking in education, which has recently focused on school system change and, 2) school leadership research, which has recently attended to the effects of leadership interventions to school improvement. Using a complexity-thinking framework, the purpose of this study was to understand how leadership practices contribute to shaping change in school systems and how change occurred across the system. Our study was conducted in an urban centre in Alberta within a public-school jurisdiction and in an area of the city that had a high population of students from culturally and linguistically diverse backgrounds from low-income households compared to other areas across the school jurisdiction. Students in this area typically scored in the lowest quartile on provincial standardized examinations. Our findings are significant because complexity thinking in the context of school leadership has not received sufficient empirical attention. In our study we identified and described pedagogical leadership practices that play a central role in redressing disparities currently found in schools.